Increased myo-inositol level in dorsolateral prefrontal cortex in migraine patients with major depression. (July 2015) - Lirng, Jiing-Feng; Chen, Hung-Chieh; Fuh, Jong-Ling; Tsai, Chia-Fen; Liang, Jen-Feng; Wang, Shuu-Jiun
Background: Although the comorbidity between migraine and major depressive disorder (MDD) has been recognized, the pathophysiology remains unclear. The dorsolateral prefrontal cortex (DLPFC) is a well-known neural substrate for MDD. We investigated the relationship between brain metabolites in DLPFC and comorbid MDD in migraine patients. Methods: We recruited migraine patients from a tertiary headache clinic. A board-certified psychiatrist conducted a structured interview for MDD diagnosis. The severity of depression was evaluated by the Beck Depression Inventory (BDI). Thirty migraine patients (five men, 25 women; mean age: 40.4 ± 12.4 years) completed the study, and 16 of them were diagnosed with MDD. All patients underwent a magnetic resonance spectroscopy (MRS) examination focusing on bilateral DLPFC. The ratios of N-acetylaspartate (NAA), choline (Cho), and myo-inositol (mI) to total creatine (tCr) were compared between migraine patients with and without MDD, and were correlated with BDI scores. Results: Relative to patients without MDD, migraine patients with MDD had higher mI/tCr ratios in the bilateral DLPFC ( p = 0.02, left; p = 0.02, right, Mann-Whitney U test). The mI/tCr ratios in the right DLPFC were positively correlated with BDI scores ( r = 0.52, p = 0.003). The NAA/tCr and Cho/tCr ratios did not differ between migraine patients with and without MDD. Conclusion: Increased mI/tCr within the DLPFC might be associated with the presence of MDD in migraine patients.